Hydrotherapy Intervention for Patients Following Total Knee Arthroplasty: A Systematic Review - Zhuo, Youguang; Yu, Rongguo; Wu, Chunling; Zhang, Yiyuan (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2021)
Background Hydrotherapy or aquatic exercise has long been known as a source of postoperative rehabilitation proposed in routine clinical practice. However, the effect on clinical outcome as well as the optimal timing of hydrotherapy in patients undergoing total knee arthroplasty (TKA) remain unclear. The purpose of this review was to assess the influence of aquatic physiotherapy on clinical outcomes and evaluate the role of the timing of aquatic-therapy for clinical outcomes after undergoing TKA.Methods An extensive literature search was performed in Embase, PubMed, and the Cochrane Library for randomized controlled trials (RCTs) that evaluated the impact of hydrotherapy on patients after TKA. The methodological quality of the trials was evaluated based on the Cochrane Risk of Bias Tool.Results All available studies on postoperative hydrotherapy after TKA were included. The primary endpoint was to evaluate the effect of hydrotherapy on clinical outcomes. The secondary outcome was to explore the role of the timing of aquatic therapy for clinical outcomes following TKA.Conclusion Although definitive conclusions could not be reached due to insufficient data, most studies indicated that participants benefited from aquatic-therapy in muscle strength, rather than gait speed, after TKA. Currently available data demonstrated that early postoperative hydrotherapy possessed a greater potential to improve clinical outcomes in main clinical scores and quality-adjusted life years (QALYs).Hintergrund Hydrotherapie oder Wassergymnastik ist seit langem als Therapieoption in der postoperativen Rehabilitation bekannt und ist Teil der klinischen Routinepraxis. Die Auswirkung auf das klinische Ergebnis sowie der optimale Zeitpunkt für eine Hydrotherapie bei Patienten nach einer Knietotalendoprothese (Knie-TEP) sind jedoch noch unklar. Ziel dieser Übersichtsarbeit war es, den Einfluss von Physiotherapie im Wasser auf das klinische Ergebnis sowie die Rolle des Zeitpunkts einer Wassertherapie für das klinische Ergebnis nach einer Knie-TEP zu bewerten.Methoden Es wurde eine umfangreiche Literatursuche in Embase, PubMed und der Cochrane Library nach randomisierten kontrollierten Studien (RCTs) durchgeführt, die den Einfluss von Hydrotherapie auf Patienten nach Knie-TEP evaluierten. Die methodische Qualität der Studien wurde anhand des Cochrane Risk of Bias Tools bewertet.Ergebnisse Alle verfügbaren Studien zur postoperativen Hydrotherapie nach Knie-TEP wurden eingeschlossen. Der primäre Endpunkt war die Bewertung der Wirkung einer Hydrotherapie auf das klinische Ergebnis. Der sekundäre Endpunkt war die Untersuchung der Rolle des Zeitpunkts einer Wassertherapie für die klinischen Ergebnisse nach Knie-TEP.Schlussfolgerung Obwohl aufgrund der unzureichenden Datenlage keine endgültigen Schlussfolgerungen gezogen werden konnten, deuteten die meisten Studien darauf hin, dass die Teilnehmer nach Knie-TEP von der Aquatherapie eher in Bezug auf die Muskelkraft als auf die Ganggeschwindigkeit profitierten. Die derzeit verfügbaren Daten zeigten, dass eine frühe postoperative Hydrotherapie eher eine Verbesserung der klinischen Ergebnisse in den wichtigsten klinischen Scores und qualitätskorrigierten Lebensjahren (QALYs) bewirken konnte.
Keywords: Aquatic exercise; Hydrotherapy; Rehabilitation; Systematic review; Total knee arthroplasty